Economic Evaluation of Dapagliflozin in the Treatment of Patients With Heart Failure: A Systematic Review - Meiyu Wu; Meiyu Wu; Shuxia Qin; Shuxia Qin; Liting Wang; Liting Wang; Chongqing Tan; Chongqing Tan; Ye Peng; Ye Peng; Xiaohui Zeng; Xia Luo; et al. (Frontiers Media S.A., 2022)
Objective: The objective of this study is to systematically review the economic evaluations of dapagliflozin in the treatment of patients with heart failure (HF) and describe their general and methodological features.Methods: This systematic review followed the PRISMA guidelines. MEDLINE/PubMed, Website Of Science, Embase, The Cochrane Library, ScienceDirect, CNKI, and Wanfang databases were searched to collect relevant studies, and the retrieval time ended on 31 October 2021. Articles on the economic evaluation of dapagliflozin in the treatment of heart failure were included. Secondary studies, incomplete economic indicators, and non-English-language and non-Chinese-language studies were excluded. Standard drug treatment was selected as the comparison. Basic characteristics, methods, and main results were extracted and analyzed systematically.Result: A total of eight studies were identified, and the overall quality was accepted, which were performed in nine developed countries (Austria, United States, Korea, Japan, Singapore, Spanish, Germany, and United Kingdom) and three developing countries (the Philippines, Thailand, and China). With the exception of the Philippines, the remaining countries considered that dapagliflozin was cost effective. In the analyses of all included studies, the incremental cost-effectiveness ratios were most sensitive to the cost of dapagliflozin, cardiovascular mortality, the duration of dapagliflozin effectiveness, and the probability of HF hospitalization.Conclusion: Dapagliflozin in the treatment of patients with heart failure with reduced ejection fraction was considered cost effective. Further studies are needed to evaluate the comprehensive value of dapagliflozin on HF.